E-Commerce E-commerce Swalayan Salafiyah pada Kopontren Musa’adah dengan Implementasi CRM (Customer Relationship Management) Untuk meningkatkan kepuasan konsumen Serta pelayanan - mohammad qosim al kamil (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Kopontren Musa'adah is a company that has various sales units, one of which is the Salafiyah Supermarket. Along with the development of the times, many shops want to compete in the field of sales. Currently, the sales system used at the Salafiyah Supermarket Shop still uses a simple method, namely the seller serves directly to customers without ordering funds, there is no distinction between customers and consumers. One of the sales strategies so that the Salafiyah Supermarket store can retain existing customers and increase customer satisfaction, the system that must be built is e-commerce by implementing the CRM (Customer Relationship Management) method.The purpose of making this system is to facilitate the sale of goods and facilitate the marketing of merchandise online while implementing CRM strategies so that customers can easily get information about promo items by sending notifications on the customer's whatsApp.this system uses the Waterfall method.The results of the study are that the system can improve service quality and strengthen relationships between customers and stores